Impacts on Ocean Worlds Are Sufficiently Frequent and Energetic to Be of Astrobiological Importance - Shannon M. MacKenzie; Alexandra Pontefract; R. Terik Daly; Jacob J. Buffo; Gordon R. Osinski; Christopher J. Cline II; Mark J. Cintala; Kathleen L. Craft; Mallory J. Kinczyk; Joshua Hedgepeth; Sarah M. Hörst; Abel Méndez; et al. (The Planetary Science Journal, 2024)
Evidence for the beneficial role of impacts in the creation of urable or habitable environments on Earth prompts the question of whether meteorite impacts could play a similar role at other potentially urable/habitable worlds like Enceladus, Europa, and Titan. In this work, we demonstrate that to first order, impact conditions on these worlds are likely to have been consistent with the survival of organic compounds and/or sufficient for promoting synthesis in impact melt. We also calculate melt production and freezing times for crater sizes found at Enceladus, Europa, and Titan and find that even the smallest craters at these worlds offer the potential to study the evolution of chemical pathways within impact melt. These first-order calculations point to a critical need to investigate these processes at higher fidelity with lab experiments, sophisticated thermodynamic and chemical modeling, and, eventually, in situ investigations by missions.